Non-destructive testing of metallic specimens using "C" scan ultrasonic procedures - Ong, Jeremy Zee Boon (Nanyang Technological University, 2020)
Ultrasonic technique using an automated C-scan over the years has established an important role as the primary inspection method for materials due to the advantages that it brought. The principles of ultrasonic inspection, different types of defects that may be created during service and/or fabrication, and their detection using ultrasonic techniques are explained in this paper. In this paper ultrasonic C-scan techniques for Non-Destructive Testing (NDT) of aluminum are developed and applied, with a sole purpose to trace pre-determined defects. There will be two types of materials to be examined; traditionally fabricated aluminum block and 3D Printed aluminum block. Specific artificial defects were embedded into the test specimen, varying in “gap” distance. Test plates were examined by C-Scan using UltraTek ultrasonic system with UltraTek Ultrasonic V5 software and common examination procedures such as full-width examination and layer to layer examination, etc. were applied to examine and characterize defects. Appropriate software tuning protocols and experimental strategies were applied, to ensure developed and optimized data obtained. These efforts aim to obtain an accurate C-scan image, allowing the detection or even the shape of the defects. Emphasis is placed on the studies on capabilities and limitations of ultrasonic techniques based on evaluating the scanned images obtained at the end of the experiment.